Relationship between Nonalcoholic Fatty Liver Disease and Vitamin D in Nepal - Sah, Manoj Kumar; Shrestha, Ramila; Shrestha, Bishnu; Khadka, Diwas (Nepal Mediciti Medical Journal, 2021)
Background and Aims: Vitamin D deficiency has been frequently reported in many causes of chronic liver disease and has been associated with the development and evolution of non-alcoholic fatty liver disease (NAFLD).The study was done to explore associations between serum vitamin D concentrations among obesity, diabetes mellitus, hypothyroidism, and metabolic syndrome and its effects on liver fibrosis by ultra-sonogram and 2 d shear wave elastography in patients with non-alcoholic fatty liver disease (NAFLD). Methods: A hospital based prospective observational study was conducted from May 2019 for twelve months period in Gastroenterology Unit, NAMS, Nepal. Seventy patients with known fatty liver identiﬁed by Ultrasonogram criteria were enrolled. All patients were evaluated by different ﬁbrosis scores (NAFLD Fibrosis, FIB4, APRI, AST/ALT ratio) and 2d shear wave score. Patients were evaluated for Vitamin D level and its effects on obesity, diabetes mellitus, thyroid related disease, dyslipidemias and NAFLD. Results: Among 70 patients, 39 (55.7%) were male and 31 (44.3%) were female with mean age of 44.3 years. Most of the patients were overweight with mean BMI of 28.2 kg/m2; among them 51 (72.9%) were more than 25.kg/m2. About 41.4% had diabetes mellitus, 77.1% had hypertension, 30% had hypothyroidism and 25.9% had metabolic syndrome. Majority of patients on ultrasound grading were mild with 64.28%; 25.72% were moderate and only 10 % were in severe groups. A study of 2 d shear wave elastography showed mean fibrosis of 7.07 kpa for mild grade, 8.22 kpa for moderate grade and 18.16 kpa for severe grade. The mean value of vitamin D was 22.61iu/ml for mild grade, 24.89 iu/ml for moderate grade and 17.4 iu/ml for severe grade. Conclusion: The results of this study showed high prevalence of serum 25(OH) vitamin D inadequacy in individuals with obesity, diabetes mellitus, hypothyroidism and metabolic syndrome which worsens as the stage of liver disease progresses.